Immunohistochemical analysis of p53 in vulval intraepithelial neoplasia and vulval squamous cell carcinoma - Rosenthal, A N (Nature Publishing Group, 2003)
Human papillomavirus (HPV) is thought to cause some vulval squamous cell carcinomas (VSCC) by degrading p53 product. Evidence on whether HPV-negative VSCC results from p53 mutation is conflicting. We performed immunohistochemistry for p53 product on 52 cases of lone vulval intraepithelial neoplasia (VIN), 21 cases of VIN with concurrent VSCC and 67 cases of VSCC. We had previously performed HPV detection and loss of heterozygosity (LOH) analyses on these samples. Abnormal p53 immunoreactivity (p53-positive) rates in HPV-positive VSCC and HPV-negative VSCC were 22% (12/54) and 31% (4/13), respectively (P<0.74). p53 immunoreactivity was associated with LOH at the p53 locus (P<0.004), but neither technique differentiated between HPV-positive and HPV-negative VSCC. p53 immunoreactivity was associated with overall LOH rates (p53-positive VSCC vs p53-negative VSCC mean fractional regional allelic loss 0.41 vs 0.24, respectively, P<0.027). LOH at 3p25 was more frequent in p53-positive VSCC cf p53-negative VSCC (70 vs 21%, respectively, P<0.007). There was a trend in p53 disruption associated with invasive disease; HPV-positive VSCC demonstrated more disruption than VIN associated with VSCC, which had more disruption than lone VIN III (22 vs 10 vs 0%, respectively, P<0.005). In all, three out of 73 cases of VIN were p53-positive. All three were associated with concurrent or previous VSCC. Meta-analysis of previous studies revealed significantly more p53 disruption in HPV-negative VSCC cf HPV-positive VSCC (58 vs 33%, respectively; P<0.0001). p53 immunoreactivity/mutation in VIN only appeared in association with VSCC. These data suggest that HPV-independent vulval carcinogenesis does not exclusively require disruption of p53, p53 disruption may work synergistically with LOH at specific loci and p53-positive VIN should be checked carefully for the presence of occult invasion.